2013
DOI: 10.1007/s00603-013-0441-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Brazilian Tests of Granite Under Coupled Static and Dynamic Loads

Abstract: Rocks in underground projects at great depth, which are under high static stresses, may be subjected to dynamic disturbance at the same time. In our previous work (Li et al. Int J Rock Mech Min Sci 45(5):739-748, 2008), the dynamic compressive behaviour of pre-stressed rocks was investigated using coupled-load equipment. The current work is devoted to the investigation of the dynamic tensile behaviour of granite rocks under coupled loads using the Brazilian disc (BD) method with the aid of a high-speed camera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(54 citation statements)
references
References 34 publications
2
52
0
Order By: Relevance
“…1. From a macroscopic point of view, the bending of the roof induces tensile stress at the roof of the opening; from a microscopic view, the discontinuities in the rock result in tensile stress locally around the opening, so the dynamic tensile failure of rocks under pre-tension has been investigated by researchers (Wu et al 2015;Zhou et al 2014). However, the far-field rocks under hydrostatic pressure can also fail in tension under dynamic loads.…”
Section: Introductionmentioning
confidence: 98%
“…1. From a macroscopic point of view, the bending of the roof induces tensile stress at the roof of the opening; from a microscopic view, the discontinuities in the rock result in tensile stress locally around the opening, so the dynamic tensile failure of rocks under pre-tension has been investigated by researchers (Wu et al 2015;Zhou et al 2014). However, the far-field rocks under hydrostatic pressure can also fail in tension under dynamic loads.…”
Section: Introductionmentioning
confidence: 98%
“…The main failure mechanism in this case is tensile splitting of the rock matrix, and the corresponding tensile strength can be deduced. Zhou et al (2014) recorded the crack growth process by using a high-speed camera in dynamic Brazilian tests of granite. The initial crack propagated from the disc center to the boundary, which shows similar crack growth process compare to numerical results of h = 0°and 90°.…”
Section: Fracture Pattern: Comparison Between Laboratorymentioning
confidence: 99%
“…The result shows that, by virtue of the ramped wave loading, the force equilibrium of the specimen can be effectively achieved and the rupture is precisely measured to synchronize with the peak force, both of which guarantee the quasi-static data reduction method employed to determine the dynamic flexural strength by Xu et al [21]. A series of rock cutting tests were performed to investigate the influence of back rake angle on the critical failure mode transition depth by Zhou et al [22]. It is found that the critical failure mode transition depth increases with the back rake angle.…”
Section: Introductionmentioning
confidence: 99%